2014
DOI: 10.1016/j.jrras.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, functional and sensory attributes of milk prepared from irradiated tiger nut (Cyperus esculentus L.)

Abstract: Available online xxx Keywords:Tiger nut cultivar Viscosity Total solids Sensory quality a b s t r a c t Five tiger nut (Cyperus esculentus L.) cultivars were collected from four different regions of Ghana and irradiated. The aim of this study was to evaluate some physicochemical, functional and sensory qualities of milk produced from irradiated tiger nut samples.Analysis was carried out for pH, total solids, moisture, sugar brix and viscosity. Finally the consumer acceptability of the milk prepared from the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The moisture content significantly increased with decreasing content of tiger nut from 80.33 g 100 g -1 in 100% tiger nut beverage to 84.78g 100 g -1 in 55:30:15 tiger nut/date/ginger blend. Quantitatively, the high moisture content reflects a characteristic quality of a typical beverage for thirst quenching and agrees with previously reported range of moisture content in tiger nut milk and chocolate beverage (Akande and Okunola, 2011;Okyere and Odamtten, 2014). This suggests reduced storage quality (shelf life) and increased likelihood of microbial contamination and consequently the safety of the product.…”
Section: Proximate Composition Of Tiger Nut Date and Ginger Bended Bsupporting
confidence: 89%
“…The moisture content significantly increased with decreasing content of tiger nut from 80.33 g 100 g -1 in 100% tiger nut beverage to 84.78g 100 g -1 in 55:30:15 tiger nut/date/ginger blend. Quantitatively, the high moisture content reflects a characteristic quality of a typical beverage for thirst quenching and agrees with previously reported range of moisture content in tiger nut milk and chocolate beverage (Akande and Okunola, 2011;Okyere and Odamtten, 2014). This suggests reduced storage quality (shelf life) and increased likelihood of microbial contamination and consequently the safety of the product.…”
Section: Proximate Composition Of Tiger Nut Date and Ginger Bended Bsupporting
confidence: 89%
“…Chufa tubers (dry weight) 15.9-41.2 [14,15] 20.1-41.7 [7] 1.5-9.3 [7] 15.4-19.5 [20,21] Horchata de chufa (wet weight) 2.4-3.1 [12] 2.0-3.0 [12] 0.6-1.4 [12] 9.0-10.0 [18,22] Although CT are mainly used commercially for the production of the milk-substitute HDC, their potential in the production of plant-based fermented products with similarities to yoghurt has also been recognized. Due to the high concentration of available sugars, fermentation with lactic acid bacteria (LAB) could result in yoghurt-like flavors.…”
Section: Source Oil (%) Starch (%) Protein (%) Sugar (%)mentioning
confidence: 99%
“…However, Abdel-Ahker et al reported an average of 19.5% total sugar content [ 21 ]. The total natural sugar content of HDC varies from 3.7 to 15%, depending on variety and process conditions [ 18 , 22 ]. See Table 1 for an overview of the compositions of CT and HDC.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exposing tigernut-milk drink to gamma radiation in terms of its physicochemical, functional and sensory qualities was reported by Ukpabi and Ukenye [19]. The tigernut-milk drink subjected to gamma irradiation can as well be pasteurized to further reduce microbial load in the drink [39]. Implementation of Hazard Analysis and Critical Control Points (HACCP) plan and GMPs is required to drastically reduce microbial contamination of home-made tigernut beverages.…”
Section: Industrial Processingmentioning
confidence: 99%